Prevalensi Infeksi Cacing Toxocara cati pada Kucing Lokal di Wilayah Denpasar - NEALMA, SAMUYUS; DWINATA, I MADE; MADE OKA, IDA BAGUS (Indonesia Medicus Veterinus, 2013)
The purpose of this study was to determine of the prevalence of Toxocara cati in local cat (Felis catus) in Denpasar and to know the ratio of prevalence T. cati between cat that are kept by the stray in Denpasar. Samples used in this study were taken from feces of 80 cats. Feces collected in the form of pots and stored in formaldehyde 4% for samples stored for a long time. Inspection feces by the floating method and data obtained from this study are presented descriptively and analyzed with Chi-square test. It found 39 positive cats infected of T. cati or prevalence is 48,8%. Based maintenance system, which cat that are kept was found infected with 13 positive of 40 samples (32,5%) while the stray cat was found infected with 26 positive of 40 samples (65%). The difference prevalence og infection found a very significant (P<0,01) between cats that are kept by the stray. The prevalence of infection T. cati on the local cats in Denpasar showed higher in feral cats than in domestic cats.